KRITERIA DESAIN RUANG TERBUKA UNTUK OPTIMALISASI INTERAKSI SOSIAL DAN PERFORMA BISNIS DI PUSAT KULINER - Demami, Aliviana; Caesania, Nindya Alun (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Open spaces play a crucial role in creating culinary centers that are not only visually appealing but also support social interaction and optimal business performance. This research aims to identify effective open space design criteria for enhancing social interaction and business performance in culinary centers. The research method employs a qualitative descriptive approach with a comparative case study method. Data collection was conducted through field observations, visual documentation, and literature and online media reviews. The main findings of this research reveal that an ideal open space design must consider elements such as flexible layouts, comfortable and interaction-supportive furniture, lighting that creates a warm atmosphere, and cleanliness. These design criteria have proven to have a significant impact on increasing social interaction among visitors and enhancing the attractiveness of culinary centers for business actors. The implications of this research provide valuable insights for developers and managers of culinary centers in creating open spaces that are not only functional but also capable of improving the visitor experience and supporting business growth.